Spline Solution of Nonlinear Beam Problems - Çağlar, Nazan; Çağlar, Hikmet; Çağal, Behiç (My University, 2003)
Nonlinear, fourth-order boundary-value problems (special case) are solved using sixth-degree B-splines. The convergence of the method is discussed. The method is tested on two beam problems from the literature.